Diminishing returns the new politics of growth and stagnation - Baccaro, Lucio 1966-; Blyth, Mark 1967-; Pontusson, Jonas 1956- (Oxford University Press, 2022)
"The Global Financial Crisis and the following period of 'secular stagnation' have raised questions about the state of modern economics and macroeconomics in particular. This has had repercussions for social sciences that deal with economic issues. In particular in the fields of International Political Economy (IPE) and Comparative Political Economy (CPE) there is rising interest in non-mainstream macroeconomic theories (Blyth and Matthijs 2017, Baccaro and Pontussen 2016). In CPE there is a recognition that the field has in the past decades increasingly shifted to institutional and microeconomic questions and disregarded Keynesian considerations of macroeconomic instability and problems of fallacies of composition (Schwartz and Tranoy 2019). The purpose of this chapter is to give an overview of post-Keynesian economics (PKE) as a non-mainstream macroeconomic theory"--
Includes bibliographical references and index
Keywords: Wachstumsmodell; Stagnation; Wirtschaftsentwicklung; Macroeconomics; Keynesian economics; Economic development; Stagnation (Economics)